Oral and maxillofacial surgery in patients undergoing dialysis for advanced renal disease: report of five cases - Yumi Mochizuki; Hiroyuki Harada; Misaki Yokokawa; Naoya Kinoshita; Kazumasa Kubota; Tomokazu Okado; Haruhisa Fukayama (BMC, 2018)
Abstract Background Perioperativemanagement of hemodialysis patients involves many difficulties. High mortality rate and circulatory or respiratory complications in these patients were reported. However, in such reports, there is no concrete information of perioperative management in hemodialysis patients to prevent surgical complications and successful outcomes. Case presentation We retrospectively reviewed the cases of 5 hemodialysis patients who underwent oral surgery under general anesthesia between January 2005 and December 2017. Primary disease was oral squamous cell carcinoma (SCC) in 4 patients and mandibular ameloblastoma in 1 patient. Partial resection was performed in 2 cases, neck dissection in 1 case. Two cases underwent surgery including vascularized reconstruction. The patients were dialyzed the day before and after surgery for the control of fluid and electrolyte status. Patients received intraoperative and postoperative intravenous infusion of potassium-free solution at 20-40 mL/h. Erythropoiesis-stimulating agents (ESAs) were used on the day of hemodialysis during hospitalization. Nafamostat mesilate as an anticoagulant during hemodialysis were used from postoperative day (POD)1 to 7. From POD 1 to 10, cephalosporin as prophylactic antibiotics is adjusted to quarter from half the initial dose. The resuming time of oral intake was similar to that of other oral surgery patients without kidney disease. The daily intake limits of protein, salt and liquid were managed during hospitalization and no cases suffered from malnutrition. No cardiorespiratory complications occurred during the perioperative period. In a case of vascularized osteocutaneous scapular flap reconstruction, grafted scapular bone survived and scapular cutaneous flap necrotized. Necrotic tissue was debrided and split thickness skin was successfully used to cover the grafted scapular bone. Conclusions Postoperative better result could be achieved if adequate perioperative management specific to hemodialysis patients is carried out. Vascularized flap reconstruction at oral and maxillofacial region in hemodialysis patients is beneficial treatment. Even if the first flap has wound complication secondary flap reconstruction is success and aesthetically better results could be achieved by the strict wound management and debridement.